Inclusão educacional no ensino superior : estudo de caso múltiplo no Campus de Altamira da Universidade Federal do Pará (UFPA) - MACHADO, Naiane da Silva (2019)
This article presents the results of the qualitative research developed at the Federal University of Pará, Campus Altamira, in 2017. The process of implementing educational policies and actions in universities for the benefit of disabled students has advanced in recent years. Thus, this study aimed to analyze the perception on the inclusion process of two physically disabled students from the campus of Altamira-Pará. As a data collection procedure, an interview was conducted using a semi-structured questionnaire. The results showed that the process of inclusion of students with physical disabilities was gradually overcome in the campus, although all actions of overcoming and difficulties in access, respect, participation and permanence in higher education are not fully assured.